Balancing people, place and prosperity: lessons from Western Australia - Brueckner, Martin (Curtin University of Technology, 2009)
Historically, the terms ‘development’ and ‘prosperity’ have been much traded commodities and to this day are treated largely as being synonymous. This paper, based on a Western Australian experience, explores the issues surrounding economic development, focusing on questions about the sharing of social, economic and environmental costs and benefits associated with it. While the notion remains unchallenged that development leads to higher levels of prosperity, at least for some, this paper raises questions about the impacts development can have on the prosperity of local communities beyond financial resources such as community health, well-being and social cohesion. In this context, the potential for friction between government, industry and communities is highlighted in the perceived absence of a requisite balance between public costs and private gains. Case study data presented brings to light the implications conflicts such as these can have for regional sustainability and governance and help distil lessons for decision-makers confronted with industry community conflicts.